Global supervision, financial stability and risk control: a banker’s view - CROFF, D. (PSL Quarterly Review, 2013)
Studies have shown that the financial integration of industrial and developing economies can lead to more efficient allocation of resources and to greater aggregate welfare. However, this integration might also lead to greater financial instability in relation to possible massive shifts in capital. This essay considers present global financial trends, and how the international and national financial systems might be better protected from the recurrence of crises. It argues that national and international surveillance and capital requirements should be complemented by risk control models, built and managed by the banks themselves and approved by national surveillance authorities, thus avoiding distortions to market forces and orienting bank managers to more efficient risk management. JEL Codes: G18, G32